Determining force behind value premium: The case of financial leverage and operating leverage - Hafiz Muhammad Zia Ul Haq; Muhammad Sohail Shafiq; Muhammad Kashif; Saba Ameer (Journal of Risk and Financial Management, 2020)
The determining force behind the value premium is the matter of debate among the researchers. Some are of the opinion that the financial distress risk determines value premium whereas other theorize that value premium is basically the compensation for operating leverage (investment activity risk). This research provides empirical evidence on this theoretical contradiction by investigating the relationships of financial leverage (FL) and operating leverage (OL) with stock returns, the book to market ratio (B/M), and systematic risk on non-financial sector firms trading at the Pakistan stock exchange (PSE). This research empirically finds significant and direct influence of operating leverage on stock returns, the book to market ratio, and systematic risk respectively. Overall findings provide support for the theoretical models which have a linked book to market effect with operating leverage. Thus, we conclude that investment activity risk seems to be the major factor that determines value premium.
Keywords: 330; financial leverage; operating leverage; stock returns; systematic risk (Ø); value premium